iGenetics: A molecular approach - Russell, Peter J.; Russell, Peter J. (New York, Pearson, 2010)
iGenetics: A Molecular Approach reflects the dynamic nature of modern genetics by emphasizing an experimental, inquiry-based approach with a solid treatment of many research experiments. The text is ideally suited for students who have had some background in biology and chemistry and who are interested in learning the central concepts of genetics. Problem solving is a major feature of the text and students have the opportunity to apply critical thinking skills to a variety of problems at the end of each chapter. Pedagogical features such as "Principal Points," at the beginning of each chapter, and "Keynotes," strategically placed throughout the chapter, are useful learning tools. The iGenetics CD-ROM and the companion website contain 25 activities and 59 narrated animations, all of which are based on text figures, to help students visualize complex processes and challenging concepts they encounter in the main text. An intense developmental effort, along with numerous third-party reviews of both text and media, ensure the highest degree of accuracy.
Glossary 707-721p.; Index 805-828p.
Keywords: Carrier detection; Chromosomes theory of inheritance; Molecular phylogeny; Statistical tools; Semiconservative DNA replication